Disorder of Sexual Development in a French Bulldog (78, MALE XX) - Ribeiro Sambatti, Natália; Wagner Silva, Vinícius; Martins de Souza Amaral, Luana; Rodrigues Greghi, Julia; dos Santos Silva, Letícia Amanda; Evani Silva De Oliveira, Thalita; de Aguiar, Ariel; Mello Martins, Maria Isabel (Acta Scientiae Veterinariae, 2024)
Background: Differentiation of the genital system occurs through a chronological sequence of events involving the determination of chromosomal, gonadal, and phenotypic sex. Disorders of sexual development (DSDs) include chromosomal sex abnormalities, gonadal abnormalities, and phenotypic variations. The purpose of this case report was to demonstrate the clinical signs and diagnosis by histopathology, immunohistochemistry, and karyotyping of a DSD in a French Bulldog (XX, male). Case: A 7-month-old phenotypically female French Bulldog with a history of clitoral hypertrophy and no signs of puberty is reported. The animal presented with a 3 cm micropenis protruding from the vulvar labia, causing discomfort and constant licking. Pelvic radiography confirmed the presence of a penile bone, supporting the differential for a disorder of sexual development (DSD). There were no abnormalities of the vaginal canal or urethral orifice. The animal underwent exploratory celiotomy to remove 2 uterine horns and their respective gonads, followed by clitoridectomy via episiotomy. Sex reversal was confirmed by histology, as seminiferous tubules and bilateral hypoplastic epididymides were identified on ovarian topography. Immunohistochemistry of gonadal tissues was positive with antibodies to progesterone and estrogen receptors, but negative with polyclonal androgen receptors and prostate-specific antigen. Karyotyping revealed XX sex chromosomes. Discussion: This dog was diagnosed as an XX DSD male (DSD 78, testicular XX) due to the presence of abdominal testes, uterus, predominantly female external genitalia with vulva and micropenis, and female sex chromosomes. Six cases of DSD have recently been reported in phenotypically female French Bulldogs due to the presence of clitoral hypertrophy or a micropenis with an atypical location. The increase in cases in this breed may be due to its popularity and increased consanguinity. Animals with clinical suspicion of DSD show signs during puberty and most of these animals tend to have a history of externalized structure in the vulva without signs of urethral and vaginal canal obstruction. In animals with ambiguous genitalia and DSDs, the estrous cycle may be normal, absent, or irregular. Because of the discomfort in the clitoral region, clitoridectomy is the 1 st line of treatment to prevent self-mutilation and future cases of vaginitis, and gonadectomy is also performed to prevent future uterine disorders and gonadal and mammary carcinogenesis. It is not uncommon for XX male animals to be unilateral or bilateral cryptorchids, in this case, both testes were in the abdominal cavity, and the animal had a normal uterus. Several alternative procedures can be performed for a better understanding of DSDs, namely: histopathology; immunohistochemistry or hormone dosage; karyotyping; and molecular analyses. These tests are important to determine the genetic sex of an animal and to confirm its concordance with the phenotypic sex. There is no evidence of interference of specific genes in the phenotypic expression of XX males, suggesting that the factors involved in their occurrence are still unknown. The hereditary nature of this disorder has not been ruled out and there are currently no laboratory tests available to identify carriers. It is recommended that cases of DSD be thoroughly investigated using complementary examinations to ensure accurate categorization of each disorder. Keywords: clitoral hypertrophy, ambiguous genitalia, immunohistochemistry, cytogenetics, sexual dimorphism.